Detailed alluvial fan geomorphology in a high-arctic periglacial environment, Svalbard: application of unmanned aerial vehicle (UAV) surveys - Aleksandra M. Tomczyk; Marek W. Ewertowski; Monika Stawska; Grzegorz Rachlewicz (Journal of Maps, 2019)
A 1:850 detailed map of the geomorphology of the Dynamisk Creek alluvial fan on Svalbard was produced based on very high-resolution data collected using an unmanned aerial vehicle (UAV) in 2014. The map documents features within the surface of the fan (0.35 km2), emphasizing their relative temporal activity. Fluvial flows were the most important geomorphological processes responsible for aggradation and modification of the fan surface. However, at present most of the fan area is inactive (about 75% of the whole fan surface) and stabilized by vegetation and mosses. Furthermore, in some places, niveo-aeolian (6% of the fan surface) and snow avalanches (1.5% of the fan surface) deposits have been noticed. In addition to the map, detailed morphometric characteristics of the fan and its catchment are also provided. The presented work illustrates the enormous usefulness of small UAVs for the study of fan surfaces in periglacial environments.